Analysis of Cultivated Land Quality Improvement Technologies - Fan, Hongjian; Shi, Lei (International Journal of Natural Resources and Environmental Studies, 2025)
This paper comprehensively reviews the research status of cultivated land quality improvement technologies, elaborates on the existing technical achievements in detail, deeply analyzes the difficulties in the application process, and puts forward prospects for the future development direction. Through a comprehensive analysis of the research progress in key fields such as soil improvement, irrigation and drainage, fertilization, and farmland ecological protection, it aims to provide a theoretical basis and practical reference for further promoting the improvement of cultivated land quality, ensuring national food security, and sustainable agricultural development.